Helium Dielectric Barrier Discharge Plasma Jet (DBD Jet)-Processed Graphite Foil as Current Collector for Paper-Based Fluidic Aluminum-Air Batteries - Chung-Yueh Shih; I-Chih Ni; Chih-Lin Chan; Cheng-Che Hsu; Chih-I Wu; I-Chun Cheng; Jian-Zhang Chen (Energies, 2022)
A helium (He) dielectric barrier discharge plasma jet (DBD jet) was used for the first time for treating graphite foil as the current collector of a paper-based fluidic aluminum-air battery. The main purpose was to improve the distribution of the catalyst layer through modification and functionalization of the graphite foil surface. The plasma functionalized the graphite foil surface to enhance the wettability where the more hydroxyl could be observed from XPS results. The 30 s-He DBD jet treatment on the graphite foil significantly improved the battery performance. The best current density of 85.6 mA/cm2 and power density of 40.98 mW/cm2 were achieved. The energy density was also improved to 720 Wh/kg.